Seletividade de inseticidas reguladores de crescimento a Podisus connexivus Bergroth, 1891 (Heteroptera: Pentatomidae) - Zacarias, Maurício Sérgio (1995)
The state of Minas Gerais presents the largest reflorestation área in Brasil, mainly with species from the Eucalypius genus. Being an exotic species, the eucalyptus allows an advantageous adaptation of phytophagous insects which live in native plants from the myrtaceae family, due to its agroechosystem fragility and for being a constant food source. The defoliator lepidopteros are considered the key pests of this culture. Predators from the Podisus genus have been researched and used in eucalyptus Integrated Pest Management programs, mainly for focus control. Among the predators, Podisus connexivus Bergroth, 1891 (Heteroptera: Pentatomidae) presents high potenciais due to its easy laboratory rearing. Thus this work had as a goal to determine the selectivity of growth regultors insecticides to eggs, nymphs and adults of the predator P. connexivus aiming to subsidize IPM - Eucalyptus programs. The insecticides tested were: triflumuron, chlorfluazuron, flufenoxuron, diflubenzuron, tebufenozide, teflubenzuron and deltamethrin. The insecticides were applied on the insect at different phases and instars via pulverization tower. Entirely casual delineation was adopted with 8 trataments (7 insecticides and 1 control) and 4 repetitions for eggs and nymphs up to the fourth instar and 3 repetitions for fífth instar nymphs and for adults. The characteristics evalueted were: viability of eggs and nymphs on the instar subsequent to the treatment and, in the adult phase, the number of eggs, the number of egg layings and eggs viability. The data were transformed, when necessary, to √X +0,5 or arc-sin √%/100 and the averages compared by the Duncan test at 5%. The results obtained revealed that the tested insecticides did not present an egg mortality, none of the products affected the oviposition or the adult eggs viability, the first instar was the most sensitive and the tebufenozide was the most selective to the predator which should be the recomended one for IPM - Eucalyptus.